COMPARISON URINE NEUTROPHIL GELATINASE – ASSOCIATED LIPOCALIN WITH STANDARD PARAMETERS IN MONITORING ACTIVITY LUPUS NEPHRITIS - CLASS IV - Rabrenović, Dr sc. med. Violeta; Petrović, Milica; Rabrenović, Milorad (Journal of Medical Biochemistry, 2022)
Introduction:  Lupus nephritis (LN) is one of the most serious complications in the development of systemic lupus erythematosus, that can adversely affect the course and prognosis of this autoimmune disease. Therefore, monitoring the effect of applied therapy, achieving remission, or monitoring LN activity is still a great challenge for nephrologists. This study aimed to compare the urinary  neutrophile gelatinase associated lipocalin  (u/NGAL)   with traditionally accepted parameters for LN activity to indicate the importance of its determination in these patients.Methods: The study group consisted of 40 patients, who were prospectively followed for a period of 4 months within three control visits  to 2 months. The first group (20/40) had active LN (Group A), and the second group had LN in remission (Group B). The parameters were compared: proteins/s, albumins/s, C3, C4, anti-ds-DNA Ab, proteinuria 24h, ur.protein / creatinine ratio - Up / cre, u/NGAL (immunochemical method CMIA),GFR. Results: Comparing standard parameters of disease activity and NGAL/u between groups, a statistically significant difference was obtained (p
Keywords: lupus nephritis; activity; neutrophil gelatinase-associated lipocalin,; proteinuria